FGF9 mutation causes craniosynostosis along with multiple synostoses. Issue 11 (25th July 2017) - Rodriguez‐Zabala, Maria; Aza‐Carmona, Miriam; Rivera‐Pedroza, Carlos I.; Belinchón, Alberta; Guerrero‐Zapata, Isabel; Barraza‐García, Jimena; Vallespin, Elena; Lu, Min; del Pozo, Angela; Glucksman, Marc J.; Santos‐Simarro, Fernando; Heath, Karen E.
Abstract: Craniosynostosis is commonly caused by mutations in fibroblast growth factor receptors (FGFRs), highlighting the essential role of FGF‐mediated signaling in skeletal development. We set out to identify the molecular defect in a family referred for craniosynostosis and in whom no mutation was previously detected. Using next‐generation sequencing, we identified a novel missense mutation in FGF9 . Modeling based upon the crystal structure and functional studies confirmed its pathogenicity showing that it impaired homodimerization and FGFR3 binding. Only one FGF9 mutation has been previously reported in a multigeneration family with multiple synostoses (SYNS3) but no signs of craniosynostosis. In contrast, our family has a greater phenotypic resemblance to that observed in the Fgf9 spontaneous mouse mutant, elbow‐knee‐synostosis, Eks, with both multiple synostoses and craniosynostosis. We have demonstrated for the first time that mutations in FGF9 cause craniosynostosis in humans and confirm that FGF9 mutations cause multiple synostoses. Abstract : Second reported FGF9 mutation. Reduction in FGF9 dimerization and binding to FGFR3. FGF9 mutations can cause craniosynostosis and/or multiple synostosis.